2012
DOI: 10.1007/bf03262474
|View full text |Cite
|
Sign up to set email alerts
|

Anticoagulant Use, the Prevalence of Bridging, and Relation to Length of Stay among Hospitalized Patients with Non-Valvular Atrial Fibrillation

Abstract: Objective: The objectives of this study were to describe inpatient anticoagulation and bridging in patients with non-valvular atrial fibrillation (NVAF) and to identify whether differences exist in length of stay (LOS) among bridged versus non-bridged NVAF patients.Design: Administrative claims data were used to select patients ≥18 years with a primary or secondary discharge diagnosis of NVAF and inpatient warfarin use from 1 July 2004 to 30 September 2009. Patients with valvular or transient causes of NVAF or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…21 However, two other studies showed that the extent of use of anticoagulant was 76-79%. 29,30 Anti platelets prescribed in 30.63% patients in our study was similar to study in United States where 45.9% patients were prescribed antiplatelets. 31 However, one study in China showed that 73.4% patients were prescribed antiplatelets.…”
Section: Discussionsupporting
confidence: 84%
“…21 However, two other studies showed that the extent of use of anticoagulant was 76-79%. 29,30 Anti platelets prescribed in 30.63% patients in our study was similar to study in United States where 45.9% patients were prescribed antiplatelets. 31 However, one study in China showed that 73.4% patients were prescribed antiplatelets.…”
Section: Discussionsupporting
confidence: 84%
“…This study suggests that heparin bridging may not be needed during the initiation of OAC in NVAF patients. The frequency of heparin bridging is reported to range from 5% to 64% in several retrospective studies [12][13][14][15], and it is 19.6% in this study. However, the actual incidence of heparin-bridging therapy in warfarin-na€ ıve patients remains unknown.…”
Section: Heparin-bridging Therapy At Oac Initiationmentioning
confidence: 46%
“…However, the actual incidence of heparin-bridging therapy in warfarin-na€ ıve patients remains unknown. A recent study by Smoyer-Tomic et al reported that 64% of 3037 hospitalized patients with NVAF received bridging therapy [14,15], and most patients had no evidence of warfarin use in the 6-month period before hospitalization. Therefore, newly diagnosed NVAF patients seem to have received OAC with a considerable proportion of concurrent heparin-bridging therapy in real-world practice, especially if they were hospitalized.…”
Section: Heparin-bridging Therapy At Oac Initiationmentioning
confidence: 99%
See 1 more Smart Citation
“…Adoption of a low intensity UFH regimen in hospitalized AF patients requiring bridging would reduce any bleeding in approximately 6400 patients and major bleeding in approximately 4200 patients per year in the United States. This is based on an extrapolation from 326 000 000 million Americans, 2115 AF hospitalizations per 1 million US population per year (assuming a 14.4% relative increase from 2010 statistics), 48% of AF patients being anticoagulated with 64% of those being bridged and 54% of them using UFH, equating to 114 411 AF patients being bridged with UFH per year. Applying the results of this study, a 5.6% absolute reduction in any bleed and 3.7% absolute reduction in major bleeds, would estimate the bleed events averted as noted above.…”
Section: Discussionmentioning
confidence: 99%